Shariah-Based Ethical Frameworks and Their Role in Shap-ing Islamic Finance in Asia: A Systematic Literature Review - Nurul Syafiqah Azman; Affendy Abu Hassim; Said Nasser Al-Amrani; Nasib Nasib; Muhammad Fathoni (YAYASAN BINA BISNIS NUSANTARA MEDAN, 2026)
The purpose of this research is to examine the role played by regional ethical codes in Islamic banking's development, adoption and the integration of this financial system at the international level. A comprehensive review of the last 6 years' research in the field is given, covering 86 academic papers from 2020 to 2025. The PRISMA methodology is applied in order to identify, appraise and merge the findings from the studies in areas like ethical and cultural values, Shariah compliance, governance, and socio-economic goals. In fact, research shows that regional ethical frameworks are crucial in ensuring that Islamic financial services are truly ethical and in addition are a key factor in differentiating Islamic financial services from conventional ones within the global marketplace. In the integration of Islamic finance with global norms there are a number of challenges, including the integration of Islamic finance with community-based ethics, the need to harmonise Islamic law with transnational financial dealings and the impact of technological advancements such as the development of financial services companies (fintech). The key theme in this study is the integration of Islamic financial practices with the values of their community, the strategies employed by financial institutions to reconcile local Shariah law with international finance systems, and the role of ethical governance in establishing trust and promoting economic growth. In light of these implications, it is essential that regulatory agencies, industry leaders and government officials work towards ensuring international business practices align with local standards of ethics. Further research is required in such areas as the implications of sustainable finance for conventional financial structures, digitalisation and its impact on the role of the business community and the finance industry, and in cross border issues of ethics.